Evaluation of Sexual Dysfunction in Patients with Hematological Malignancies - Yasemin Karacan; Hicran Yildiz; Burcin Demircioglu; Ridvan Ali (Asia-Pacific Journal of Oncology Nursing, 2021)
Objective: Physiological and/or psychological problems that affect the quality of life of the patients occur depending on the diagnosis and treatment of hematological malignancies. Cancer treatment causes sexual problems such as infertility, vaginal dryness, and erectile dysfunction in the patients. Erectile dysfunction and loss of sexual desire are the most common sexual problems of men, while dyspareunia and loss of sexual desire are the most common sexual problems of women. This descriptive study was carried out to evaluate sexual problems and affecting factors in the patients with hematological cancer. Methods: Between July 1, 2011, and July 31, 2011, 45 sexually active patients who volunteered to participate in the study and whose written consents were obtained were included in the study. The data of the study were collected using the descriptive characteristics form prepared by the researchers based on the relevant literature and the Arizona Sexual Experiences Scale (ASEX). The scale scores range from 5 to 30 and a score of >11 above indicates sexual dysfunction. Results: Sexual dysfunction was observed in 62.2% of the patients. About 80.0% of women and 57.1% of men had sexual dysfunction. Sexual dysfunction was observed to be highest between the ages of 52–71 (81.2%) years. The mean total ASEX score was 15.90 ± 4.25 in women and 13.34 ± 5.37 in men. The ability to reach orgasm subscale score was found to differ by gender in the ASEX scale (P < 0.05). Conclusions: The prevalence of sexual dysfunction is high in the patients with hematological malignancies. It is recommended to evaluate these patients in terms of the presence of sexual dysfunction, as in the patients with other chronic diseases.